Comparative theory and political experiences / Peter J. Katzenstein, Theodore Lowi, Sidney Tarrow - Katzenstein, Peter J. [et.al] (1990)
Physiocracy, the state, and society, the limits of disengagement, rousseau and women, and alternative reading, the liberal agenda of thefrench-itallian inquiry, exclusionary democracies, the postauthoritarian experience, the French communities party, the seeds of its own decline, communism in Western Europe, of roots, graftis, growth, and decline; comparative political economy, nationalization in France and Italy thirty years later, the revolution and the new America State